COMPARATIVE EFFECTIVENESS AND SAFETY OF METHODS OF INSULIN DELIVERY AND GLUCOSE MONITORING FOR DIABETES MELLITUS: A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Achieving glycemic control remains difficult for patients with type 1 diabetes. We compared the efficacy of day-and-night hybrid closed-loop insulin delivery to sensor-augmented pump therapy in individuals 6 years and older with suboptimally controlled type 1 diabetes. The aim: This article compared effectiveness and safety of methods of insulin delivery and glucose monitoring for diabetes mellitus. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 166 articles, whereas the results of our search on SagePub brought up 143 articles. The results of the search conducted for the last year of 2013 yielded a total 116 articles for PubMed and 89 articles for SagePub. In the end, we compiled a total of 23 papers, 15 of which came from PubMed and eight of which came from SagePub. We included six research that met the criteria. Conclusion: The use of a hybrid closed-loop insulin delivery system in free-living conditions for a period of twelve weeks led to clinically relevant improvements in glycaemic control while simultaneously reducing the risk of hypoglycemia in suboptimally controlled type 1 diabetes in adults, adolescents, and children aged six years and older.